2018
DOI: 10.3390/ijerph15040590
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Outdoor Gyms in Public Open Spaces: A Systematic Review and Integrative Synthesis of Qualitative and Quantitative Evidence

Abstract: (1) Background: An outdoor gym (OG) is environmental infrastructure built in a public open space to promote structured physical activity. The provision of OGs is increasingly seen as an important strategy to realize public health agendas promoting habitual physical activity. A systematic review was conducted to synthesize characteristics of OG and OG users’ experiences and perceptions in different cultural contexts; (2) Methods: Online searches of multidisciplinary databases were conducted in health, sport and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
38
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 28 publications
0
38
0
3
Order By: Relevance
“…In many studies, the authors prove that training on street fitness equipment is a key factor not only in recreational and corrective conditions (Allen-Collinson & Leledaki, 2015;Lee et al, 2018), but also in the physical development of athletes of various qualifications (Kharisov et al, 2017). The study enriched the process of implementing physical culture and sports activities at the place of residence (Ries et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…In many studies, the authors prove that training on street fitness equipment is a key factor not only in recreational and corrective conditions (Allen-Collinson & Leledaki, 2015;Lee et al, 2018), but also in the physical development of athletes of various qualifications (Kharisov et al, 2017). The study enriched the process of implementing physical culture and sports activities at the place of residence (Ries et al, 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Outdoor gyms seem to be acceptable even for older adults according to an Australian study which showed that forty-two percent of park users above 50 years old had used an outdoor gym [ 44 ]. Outdoor gyms seem not only to be positively evaluated by users as pursuing health [ 45 ], but also to be used on a regular basis and thus raise the level of moderate to vigorous physical activity in parks [ 46 ]. Based on a natural experiment in urban public parks, building fitness zones seems to be cost-effective (10.5 cents/MET increase) and most effective in parks in densely populated areas with few other facilities [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…To guide public health practice, ecological social models have been recommended. These describe the interactions between people and their social and physical environment (Golden & Earp, 2012;Lee, Lo & Ho, 2018). That's why the use of safe outdoor public spaces is one of the ways to improve practice of PA (McCormack, Rock, Toohey & Hignell, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…So, a popular strategy is the outdoor gym (OG) installation (Copeland et al, 2017;Del Campo, Bermúdez, Peluffo & Del Campo, 2016). An OG is defined as fixed exercise equipment placed in an outdoor area that is freely accessible to the public, to promote structured PA through strength, aerobic and stretching devices (Cohen, Marsh, Williamson, Golinelli & McKenzie,2012;Cranney, Shaw & Phongsavan, 2018;Lee et al 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation